A strong law of large numbers for harmonizable isotropic random fields. (1997) - Swift, Randall J.
Abstract : The class of harmonizable fields is a natural extension of the class of stationary fields. This paper considers a strong law of large numbers for the spherical average of a harmonizable isotropic random field.